Investigating the effect of water quality on the adsorption of a xanthate collector in the flotation of a sulphide ore - Manenzhe, Resoketswe (Department of Mechanical Engineering, 2019)
Environmental concerns necessitate the recycling of process water within mining operations. On average, recycled water contains more dissolved solids than fresh water. Since water is used as both a transportation and process medium, it is expected that changes in its quality will affect plant processes. Flotation is a process that is acutely sensitive to the immediate conditions of the system. Literature suggests that the efficiency of flotation separation is driven by the hydrophobicity that can be achieved by the mineral particles meant to be floated. The hydrophobicity is in turn driven by the adsorption of specialised reagents i.e. the collectors. Since collectors are added such that they adsorb at the liquidparticle interface, it stands to reason that changing the chemical composition of the aqueous phase will affect the collector adsorption, and hence the flotation response of target minerals. In this study, a sulphide copper ore from the Zambian Copperbelt was floated in synthetic plant waters of varying ionic strengths, and with different concentrations of the collector sodium isobutyl xanthate (SIBX). The synthetic plant waters were prepared by adding varying concentrations of inorganic salts to distilled water in order to achieve process water compositions that reflect water compositions typically found in mining plants. Additionally, a nickel-copper ore from Lapland Finland was floated in the synthetic plant waters as well actual plant waters. To account for the latter ore’s polymetallic nature, the collectors aerophine and sodium isopropyl xanthate (SIPX) were used sequentially. The objective of the study was therefore to investigate the effect of water quality on collector adsorption in the flotation of sulphide ores. The study showed that water quality has a quantifiable effect on SIBX and SIPX adsorption. The respective effects of water quality and collector adsorption on ore flotation could not be irrefutably decoupled. However, it could be concluded that of the tested waters, the copper thickener overflow was the least conducive to xanthate adsorption and valuable mineral recovery. On the other hand, collector adsorption was favoured by waters such as the raw and standard process. However, increased adsorption did not necessarily result in improved grades and recoveries. The study further showed that in the case that the dissolved ionic species are identical, increasing the ionic strength of water yields a linear decrease in xanthate adsorption, and that recycling SIPX retained in flotation waters resulted in reduced separation selectivity.